1993
DOI: 10.2337/diacare.16.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Development of Macrovascular Diseases in NIDDM Patients in Northern Taiwan: A 4-yr follow-up study

Abstract: In the prevention of macrovascular diseases, effective intervention of the nondiabetic cardiovascular risk factors may be as important as or even more important than the good control of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Although the lack of an association between smoking and CAD seemed to be contradictory to the generally accepted concept of smoking as a risk factor, no association was also noted in our previous longitudinal follow-up study for CAD incidence in patients with T2DM in Taiwan. 18 More studies are necessary to examine this somewhat interesting but paradoxical finding. The results of this study also suggested the usefulness of using WC to approximate visceral adiposity due to its significant association with CAD in the diabetic patients.…”
Section: C-h Tsengmentioning
confidence: 93%
See 2 more Smart Citations
“…Although the lack of an association between smoking and CAD seemed to be contradictory to the generally accepted concept of smoking as a risk factor, no association was also noted in our previous longitudinal follow-up study for CAD incidence in patients with T2DM in Taiwan. 18 More studies are necessary to examine this somewhat interesting but paradoxical finding. The results of this study also suggested the usefulness of using WC to approximate visceral adiposity due to its significant association with CAD in the diabetic patients.…”
Section: C-h Tsengmentioning
confidence: 93%
“…[18][19] CAD was defined by Minnesota codes of coronary probable (1.1, 1.2, 7.1) and coronary possible (…”
Section: Diagnosis Of Cadmentioning
confidence: 99%
See 1 more Smart Citation
“…'-8 - 9 Moreover, there are no prospective population-based studies evaluating metabolic control and duration of diabetes as predictors of stroke in elderly diabetic subjects. Disturbances in glucose metabolism are characterized not only by hyperglycemia but also by hyperinsulinemia, which has been found to be a risk factor for coronary heart disease in some 1011 but not all 12 studies.…”
Section: Non-insulin-dependent Diabetes and Its Metabolic Control Arementioning
confidence: 99%
“…19,20 The lack of an association in the present study (Tables 1 and 5) was consistent with our previous follow-up study for IHD incidence in patients with T2DM. 14 The effect of smoking might be more important in younger individuals than in the elderly. [21][22][23] Therefore the role of smoking on IHD in the diabetic patients with an average age of approximately 60 years in Taiwan requires further confirmation.…”
Section: Discussionmentioning
confidence: 99%